Blastoid variant of mantle cell lymphoma in palatine tonsil - Valente, Vitor Bonetti [UNESP]; de Castro, Tamara Fernandes [UNESP]; Takamiya, Aline Satie [UNESP]; Callestini, Renata [UNESP]; Xavier-Junior, José Cândido Caldeira; Cortopassi, Gabriel Macedo; Neto, Sebastião Conrado [UNESP]; Collado, Francisco Urbano [UNESP]; Biasoli, Éder Ricardo [UNESP]; Miyahara, Glauco Issamu [UNESP]; Bernabé, Daniel Galera [UNESP] (Elsevier, 2021)
Blastoid variant of mantle cell lymphoma (MCL) is an aggressive and extremely rare malignancy. MCL may be diagnosed in lymph nodes and/or extranodal sites exhibiting a poor prognosis. MCL with primary presentation in palatine tonsils has been rarely reported. Herein, we report the case of a 73-year-old man with a painless nodular mass on the right palatine tonsil. A biopsy was performed, and microscopic analysis revealed a neoplasm composed of small to medium sized lymphocytes with finely dispersed chromatin, roundish nucleus and many mitoses. The tumor cells were positive for CD20 (L26), CD5 (4C7), Cyclin D1 (EP12), Bcl2 (124) and Ki-67 (MIB-1; 90%), and negative for Bcl6 (PG-B6p), MUM1 (MUM1p) and CD3 (Polyclonal). These findings led to the diagnosis of blastoid variant of MCL. Diagnostic workup with computed tomography scan excluded other sites of disease. The patient was treated successfully with cyclophosphamide, doxorubicin, vincristine and prednisolone (mini-CHOP regimen). Although the blastoid variant of MCL is rare, it should be included in the differential diagnosis of rapid-growing masses in the palatine tonsil.
Keywords: Blastoid variant; Cancer; Diagnosis; Head and Neck lymphoma; Lymphoma; Mantle cell lymphoma; Non-Hodgkin lymphoma; Palatine tonsil lymphoma; Treatment